Complex of activation tools for energy saving measures in housing and utilities sector of the city - Trach, O. (My University, 2014)
The complex of activation instruments for energy saving measures in housing and utilities sector of the city is presented in the article. Regulatory basis that promotes the development of renewable energy in Ukraine is analyzed. Influence on the behavior of final consumers of energy is determined as the way to overcome the problem of energy efficiency. The paper analyzes the main features of energy saving measures as a complex final consumption product. The specific features of marketing to be employed for activating the use of energy saving measures in housing and utilities sector of the city are defined. Examples of using activation tools in the cities of Ukraine and Europe are given. It is shown that in order to achieve the highest efficiency in the sphere of energy saving a complex of activation instruments being adjusted to the characteristics of individual objects should be used. Key words: energy saving measures, activation tools, housing and utilities sector. Висвітлено комплекс інструментів активізування використання заходів з енергозбереження в житлово-комунальному господарстві міста. Проаналізовано нормативне підґрунтя, що сприяє розвитку відновлювальної енергетики в Україні, а також визначено, що для вирішення проблеми енергозбереження необхідно здійснювати вплив на кінцевих споживачів енергії. Проаналізовано основні риси заходів з енергозбереження як комплексного товару кінцевого споживання, а також визначено особливість маркетингу, що доцільно застосовувати для активізування використання заходів з енергозбереження в ЖКГ міста. Наведено приклади використання інструментів активізування в містах України та Європи. Визначено, що для досягнення найбільшої ефективності в сфері енергозбереження необхідно використовувати цілий комплекс інструментів активізування, пристосовуючи його відповідно до особливостей окремих об’єктів.
Комплекс інструментів активізування використання заходів з енергозбереження в житлово-комунальному господарстві міста
Keywords: energy saving measures; activation tools; housing and utilities sector; заходи з енергозбереження; інструменти активізування; ЖКГ